Constitutive relations of springs to model and simulate reinforced concrete frames - Biton, Nophi Ian D.
The study aims to propose with constitutive relations of springs that may be utilized in a model of reinforced concrete (RC) buildings using Rigid Body Spring - Discrete Element Method. An investigation of various failure mechanisms of RC beams and columns was done based from literature. The capacity of bisymmetric RC section in all force actions (axial, shear, flexure and torsion) were derived using basic theories and empirical studies. The control points of the capacity curves were used to define the nonlinear parameters of the spring corresponding to the force actions. A new spring which is capable of modeling all four basic force actions of RC was made available. The springs were tested and proven effective for simple dynamic problems. Finally, a set of failure criteria for a system of springs was proposed.